2023
DOI: 10.21203/rs.3.rs-2570204/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The multi-kinase inhibitor CG-806 exerts anti-cancer activity against acute myeloid leukemia by co-targeting FLT3, BTK, and Aurora kinases

Abstract: Background: Despite the development of several FLT3 inhibitors that have improved outcomes in patients with FLT3-mutant acute myeloid leukemias (AML), drug resistance is frequently observed, which may be associated with the activation of additional pro-survival pathways such as those regulated by BTK, aurora kinases, and potentially others in addition to acquired tyrosine kinase domains (TKD) mutations of FLT3 gene. FLT3may not always be a driver mutation. Objective: To evaluate the anti-leukemia efficacy of t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…The FLT3/BTK/Aurora kinase (AURKs) inhibitor luxeptinib (CG-806), due to its multi-target action, causes the arrest of blasts in G2/M, promotes polyploidy formation, stimulates apoptosis, and inhibits BTK-mediated autophagy, by-passing resistance to FLT3i [33]. Yu et al [34] confirmed these data in immunoblotting analyses of CG-806-treated cell lines. In fact, inhibition of AKT/mTOR/S6K and MAPK results in suppression of p-mTOR, -S6K, and -RB cell proliferation proteins, while inhibition of BTK causes upregulation of p27 and downregulation of G1 phase checkpoint proteins, such as CDK4, CDK6, and c-Myc, blocking FLT3mut cells (MOLM3 and MV14-4) in G1.…”
Section: New Approaches To Treatment Of Flt3mut Lsc Resistancementioning
confidence: 94%
“…The FLT3/BTK/Aurora kinase (AURKs) inhibitor luxeptinib (CG-806), due to its multi-target action, causes the arrest of blasts in G2/M, promotes polyploidy formation, stimulates apoptosis, and inhibits BTK-mediated autophagy, by-passing resistance to FLT3i [33]. Yu et al [34] confirmed these data in immunoblotting analyses of CG-806-treated cell lines. In fact, inhibition of AKT/mTOR/S6K and MAPK results in suppression of p-mTOR, -S6K, and -RB cell proliferation proteins, while inhibition of BTK causes upregulation of p27 and downregulation of G1 phase checkpoint proteins, such as CDK4, CDK6, and c-Myc, blocking FLT3mut cells (MOLM3 and MV14-4) in G1.…”
Section: New Approaches To Treatment Of Flt3mut Lsc Resistancementioning
confidence: 94%